2004
DOI: 10.1007/s00254-004-0986-3
|View full text |Cite
|
Sign up to set email alerts
|

Vulnerability assessment in karstic areas: validation by field experiments

Abstract: Several methods have been developed for vulnerability mapping in karstic areas. These methods need additional validation by field experiments. Several tests have been carried out in the Swiss Jura with natural and artificial tracers. The protective role of some intrinsic properties of the system, such as glacial deposits covering karst, epikarst storage and system dilution effect, have been clearly demonstrated. Use of three tracers in parallel showed the reactivity of the epikarst: all tracers arrived at the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(20 citation statements)
references
References 3 publications
0
19
1
Order By: Relevance
“…Jeannin et al (2001) proposed to use the duration of tracer appearance above a critical concentration threshold as an additional criterion. Perrin et al (2004) and Andreo et al (2006) also used tracers for the validation of vulnerability maps.…”
Section: Conceptual Basis and Proposed Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Jeannin et al (2001) proposed to use the duration of tracer appearance above a critical concentration threshold as an additional criterion. Perrin et al (2004) and Andreo et al (2006) also used tracers for the validation of vulnerability maps.…”
Section: Conceptual Basis and Proposed Methodsmentioning
confidence: 99%
“…Later on, COST Action 620 proposed a "European approach to vulnerability and risk mapping for the protection of karst aquifers" (Daly et al 2002;Zwahlen 2004). Several methods of intrinsic vulnerability mapping were developed within this framework such as the PI method (Goldscheider et al 2000), which served as a basis for the conceptual model of the European Approach, and the COP Method, a fairly complete implementation of this approach .…”
Section: Introductionmentioning
confidence: 99%
“…EPIK (Doerfliger and Zwahlen 1998), the proposed method does not explicitly include the mapping of karren, dolines and other karst landforms. Tracing-irrigation experiments and other field observations have revealed that the exokarst is not a reliable indicator for vulnerability (Goldscheider et al 2001;Perrin et al 2004). Contaminants might rapidly travel through shallow soils and the unsaturated zone even when no karst landforms are visible, while dolines and karren might be clogged with sediments and thus provide some degree of protection.…”
Section: Groundwater Vulnerability Mapping -The Duality Methodsmentioning
confidence: 99%
“…From a quantitative point of view, three aspects are important for vulnerability assessment: the travel time of a contaminant from the origin to the target, the attenuation along its pathway, and the duration of a contamination at the target (Brouyère 2004). This approach makes it possible to validate vulnerability assessments by means of artificial tracer tests, and chemical and microbiological groundwater quality data (Goldscheider et al 2001;Holman et al 2005;Perrin et al 2004). Margat (1968) introduced the term "vulnerability of groundwater to contamination", which can be used as an alternative to the term "natural protection against contamination"-the lower the natural protection, the higher the vulnerability.…”
Section: Basic Conceptsmentioning
confidence: 99%
“…Each vulnerability map should be confirmed after construction in order to estimate the validity of the theoretical sympathetic of current hydrogeological conditions [28,29]. Several methods can be applied for the validation of vulnerability assessments; these include hydrographs, chemo-graphs and tracers (natural or artificial) [30].…”
Section: Validation Of Both Modelsmentioning
confidence: 99%